Use of Instagram, Social Comparison, and Personality as Predictors of Self-Esteem - Fagundes,Luiza Seabra (2020)
Abstract In the face of a population that is increasingly connected electronically, the objective of this research was to test the predictive power of Instagram’s use intensity, social comparison and the five major personality factors of self-esteem. The survey, made available on the internet with sociodemographic questions and four scales, was answered by 625 Brazilians, of which 63.7% were women. The results indicated neuroticism and social comparison (abilities factor) as negative predictors of self-esteem. Extraversion, agreeableness, consciousness, social comparison (opinions factor), and age were shown to be positive predictors of self-esteem. For women, the higher the intensity of Instagram’s use, the lower the levels of self-esteem. The negative relationship between self-esteem and the intensity of Instagram use was mediated by social comparison (suppression effect). It is suggested that the harm of using the social network relates to the activity of comparing himself to other people.